Water-fluxed crustal melting produces Cordilleran batholiths - Collins, Bill; Huang, H.; Jiang, X. (Geological Society of America, 2016)
Most granites and related calc-alkaline silicic volcanic rocks from the United States and New Zealand Cordillera are saturated with zircon between 65 and 70 wt% SiO2. For this silica interval, zircon saturation temperatures (Tzr) are universally lower (<800 °C) than those expected by dehydration melting of mafic crust (T >900 °C). The values contrast with Tzr from alkaline rocks from the Cenozoic U.S. Cordillera, which are typically >800 °C for 65-70 wt% SiO2. Case studies of titanium-in-zircon thermometry from the U.S. Cordillera also suggest that alkaline magma injections into granitic magma chambers are hot, but calc-alkaline magma injections are usually cooler. A model is presented suggesting that silicic Cordilleran magmas form in magmatic arcs where hydrous basaltic magmas solidify in the arc root, producing mafic underplates that exsolve aqueous fluids, which transfer to the crust and promote water-fluxed partial melting at ambient pressure-temperature (~750-800 °C at 8 kbar) conditions. Subsequent rock-buffered melting reactions modulate the water content of arc magmas. The granitic partial melts are water undersaturated, rise adiabatically as increments, but stall in the middle to upper crust, building cool and hydrous, crystal-rich magma chambers (batholiths). However, injections of hotter magmas are required to drive volcanic eruption. In the backarc, granitic magma chambers are intermittently recharged with hotter, drier alkaline magmas, which are produced mostly by decompression melting during lithospheric extension, not hydrous fluxing. This highlights the control of subduction dynamics on water content and consequently magmatic temperatures in silicic magma systems.